KEDUDUKAN DAN HAK MEWARIS ANAK YANG BERSTATUS WARGA NEGARA ASING (STUDI PUTUSAN PENGADILAN TATAUSAHA NEGARA DI JAKARTA NOMOR141/G/2010/PTUN-JKT) - ERMILIA DEVRITA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin, SH, MS, CN2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Syahril Sofyan, Sh, MKn A child who is born from an international mix marriage will have a problem with his status of citizenship and with his inheritance rights. Jakarta Probate Court issued a Letter of Notifications on Inheritance Rights for a child who had foreign citizen status and stated that he was the heir of his late mother’s property. However, his mother’s siblings filed a complaint. A child who has status the status of foreign citizen has the right to inherit from his parents who are Indonesian citizens. However, if he inherits an ownership property, according article 21, paragraph 3 of Agrarian Law, he has to relinquish his rights within 1 (one) year after he inherits it. It is recommended that every Indonesian citizen should pay attention and be aware of any rules and regulations on civil registry in Indonesia so that there will be law of order.Keywords: Inheritance Rights, Foreign Citizen